2023
DOI: 10.3390/jcm12062128
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Dental Custom CAD-CAM Implant Abutments and Dental Implant Stock Abutments

Abstract: The implementation of CAD-CAM systems in dentistry has significantly influenced the evolution of dental implantology and implant-supported prosthetics within the past three decades. Implant-supported prostheses are comfortable and aesthetic. The prosthetic abutment has also faced a rapid design evolution, from the individualization of standard stock abutments offered by various manufacturers to a modern customization process using CAD-CAM technology. This paper presents a comparative study between 20 dental cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…After duplicate removal and title/abstract screening, 19 articles were selected for full-text analysis. Hence, 13 studies were excluded for the following reasons: the aim of the study was inconsistent with the aim of the systematic review [16,[26][27][28][29][30][31][32][33][34][35], overlapping data/same cohort [36] and the study design was inconsistent with the inclusion criteria [37]. The reasons for exclusion are available in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removal and title/abstract screening, 19 articles were selected for full-text analysis. Hence, 13 studies were excluded for the following reasons: the aim of the study was inconsistent with the aim of the systematic review [16,[26][27][28][29][30][31][32][33][34][35], overlapping data/same cohort [36] and the study design was inconsistent with the inclusion criteria [37]. The reasons for exclusion are available in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the use of customised abutments leads to an increase in the final abutment size, improved retention of the prosthetic work, and reduced angulation of the abutment in relation to the implant axis, thus reducing the risk of unscrewing or fracturing the dental screw. Therefore, the use of customised abutments provides stability to aesthetically compromised peri-implant tissues [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In implantology nowadays, the prosthetic phase has shown a growing inclination towards the utilization of customized abutment [ 13 ]. Our study has revealed that in recent years, customized abutments have become more frequently chosen.…”
Section: Discussionmentioning
confidence: 99%
“…CAD/CAM customized abutments have been proven to have a good aesthetic and functional prognosis of implant-supported restorations. Moreover, they contribute to enhancing the final shape of prostheses, improving the stability of implant-supported prostheses, and efficiently transmitting masticatory forces to the implant [ 13 ].…”
Section: Discussionmentioning
confidence: 99%